The relationship between pressure drop and liquid saturation in oil-mist filters - Predicting filter saturation using a capillary based model - Mead-Hunter, Ryan; Braddock, Roger; Kampa, D; Merkel, Nini; Kasper, Gerhard; Mullins, Benjamin (Pergamon, 2012)
This work details the results of a study into the relationship between pressure drop and liquid saturation in mist (or coalescing) filters. Liquid saturation (clogging) in mist filters is of critical importance as it is directly related to filter efficiency and flow resistance. Experiments were conducted to determine steady-state saturation and pressure drop values in commonly used oleophillic fibrous filter media, using a range of different combinations of face velocity and number of layers of media within the filter element. Several empirical relationships for saturation and pressure drop were derived based on the relationships found. In addition, a capillary-based saturation model has been described and fitted to the experimental data. A good agreement between the model and data was obtained when an empirically fitted term was added. Equations were developed which allow such variables to be determined from known parameters.